Occupational stress and safety culture: trends for contribution and construction of knowledge in nursing - Munhoz, Oclaris Lopes; Andolhe, Rafaela; Schimith, Maria Denise; Oliveira, Gabriela; Ribeiro, Polyana De Lima; Silva, Thayná Champe da; Cremonese, Luiza (ABCS Health Sciences, 2018)
Stress is considered to be one of the factors that affect nursing professionals the most and may disturb the safety culture and disfavor the assistance provided. The objective of the present study was to identify and characterize the tendencies of the theses and dissertations in nursing produced in Brazil about the subject of occupational stress of the nursing team associated to the safety culture. It is a narrative review study. The search was carried out in the portal of theses and dissertations of CAPES, in May 2017, without temporal cut. There was a predominance of dissertations, with a quantitative approach, in the year 2015, in the southern region. The fragility of the safety culture has been identified in studies regarding patient safety. The results also pointed to weaknesses in the actions developed and the need to implement strategies that would contribute to better health care. Still, occupational stress was recognized by professionals as a negative influence on work. Therefore, a predominance of safety culture studies in closed hospital units was revealed as a trend of production.